2017
DOI: 10.1038/cddis.2017.252
|View full text |Cite
|
Sign up to set email alerts
|

The putative tumor suppressor microRNA-30a-5p modulates clear cell renal cell carcinoma aggressiveness through repression of ZEB2

Abstract: Clear cell renal cell carcinoma (ccRCC), the most common subtype of renal cell carcinoma, can easily invade local tissues and metastasize, and is resistant to currently available treatments. Recent studies profiling microRNA expression in ccRCC have suggested miR-30a-5p may be deregulated in these cancer cells. To determine its role and mechanism of action in ccRCC, miR-30-5p expression levels were quantified and functions were analyzed using in vitro and in vivo experiments and bioinformatics. A decrease in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 44 publications
4
59
1
Order By: Relevance
“…In this study, we demonstrated that miR-30a-5p was repressed in ccRCC in vivo and in vitro . Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we demonstrated that miR-30a-5p was repressed in ccRCC in vivo and in vitro . Consistent with our results, in a recent elegant study, Chen et al shows that miR-30a-5p expression is restricted and the reduced expression of mir-30a-5p promotes ccRCC prognosis [31]. Von Hippel-Lindau gene (VHL) has been reported as a tumor-suppressor gene, which is associated with ccRCC [32, 33].…”
Section: Discussionsupporting
confidence: 79%
“…But why miR-30a-5p expression was decreased in ccRCC is still completely unclear. Chen et al demonstrates that the miR-30a-5p expression is regulated by long noncoding RNA (lncRNA) DLEU2 in ccRCC [31]. Previous study also demonstrates that miR-30a expression could be also regulated by the protein encoded by VHL [34].…”
Section: Discussionmentioning
confidence: 99%
“…24 Importantly, DLEU2 could act as an endogenous sponge by directly binding to miR-30a in renal cell carcinoma. 21 Here, we confirmed the existence of an interaction between DLEU2 and miR-455 in PC cells.…”
Section: Discussionsupporting
confidence: 75%
“…Long noncoding RNA DLEU2 is downregulated in leukemia and laryngeal carcinoma . However, it was found to be elevated in renal cell carcinoma cells, and higher expression of DLEU2 was associated with a poor prognosis in patients with renal cell carcinoma . These previous results indicated that DLEU2 might have distinct functions in different tumors but did not provide enough information about the biological activity and mechanism by which DLEU2 regulates carcinogenesis and progression of human tumors (including PC).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation